Formulation of value added beef meatball using tulsi (Ocimum sanctum) leaf extract as a source of natural antioxidant (Journal of the Bangladesh Agricultural University, 2018)
The present study was undertaken to evaluate the effect of different levels of tulsi leaf extract on fresh and preserved beef meatballs. Four types of beef meatballs were formulated for this purpose. Meatballs were made with 0 (control), 0.1, 0.2 and 0.3% tulsi leaf extract, respectively and preserved at-20°C. Quality and safety evaluation of meatballs were determined by sensory, physicochemical, biochemical and microbiological tests. The analyses were conducted at 0, 15th, 30th and 60th days of interval. Considering CP, tenderness, juiciness, overall acceptability, cooking loss, Free Fatty Acid (FFA), Per oxide Value (POV) and Thiobarbituric Acid Reactive Substances (TBARS) value, it can be concluded that tulsi leaf extract @ 0.1, 0.2 and 0.3% can be used in the formulation of beef meatball. In case of sensory evaluation 0.2% tulsi leaf extract is appreciated but on the basis of nutrient quality, physicochemical properties, biochemical analysis and microbial analysis 0.3% tulsi leaf extract is more satisfactory as a source of natural antioxidant than that of other treatment groups. Therefore, it may be concluded that 0.3% tulsi leaf extract can be added as a functional ingredients in beef meatball.J. Bangladesh Agril. Univ. 16(2): 260-265, August 2018